Notes on Mesocapromys sanfelipensis (Rodentia: Capromyidae) from Cuba - López, Lazaro W. Viñola; Garrido, Orlando H.; Bermúdez, Alberto (Zootaxa, 2018)
The San Felipe Hutia, Mesocapromys sanfelipensis, is one of the most endangered species of rodents in the world, and little is known about its ecology, evolution, and ancient distribution. At present, this hutia has been found only in its type locality, Cayo Juan Garcia, a cay in the southwest Cuban insular platform. Here we report for the first time a well preserved fossil skull referred to this species, collected in Cueva del Indio, Mayabeque province, western Cuba. This specimen shows that the modern population of M. sanfelipensis is a marginal relic of its former distribution, a consequence of climatic, eustatic, and neotectonic changes in the last 8 ka years. Also, we reevaluate the cranial characters and measurements that correspond to M. sanfelipensis and found that two of the eight specimens referred to this species and deposited at the Instituto de Ecologia y Sistematica belong to Mesocapromys auritus. Finally, we include six unpublished photos of specimens of M. sanfelipensis captured in 1970 during two expeditions to Cayo Juan Garcia.